Prenatal and accurate perinatal diagnosis of type 2 H or ductular duplicate gallbladder - Umberto Maggi; Giorgio Farris; Alessandra Carnevali; Irene Borzani; Paola Clerici; Massimo Agosti; Giorgio Rossi; Ernesto Leva (BMC, 2018)
Abstract Background Double gallbladder is a rare biliary anomaly. Perinatal diagnosis of the disorder has been reported in only 6 cases, and in 5 of them the diagnosis was based on ultrasound imaging only. However, the ultrasound technique alone does not provide a sufficiently precise description of cystic ducts and biliary anatomy, an information that is crucial for a correct classification and for a possible future surgery. Case presentation At 21 weeks of gestational age of an uneventful pregnancy in a 38 year old primipara mother, a routine ultrasound screening detected a biliary anomaly in the fetus suggestive of a double gallbladder. A neonatal abdominal ultrasonography performed on postnatal day 2 confirmed the diagnosis. On day 12 the newborn underwent a Magnetic Resonance Cholangiopancreatography (MRCP) that clearly characterized the anatomy of the anomaly: both gallbladders had their own cystic duct and both had a separate insertion in the main biliary duct. Conclusions We report a case of early prenatal suspected duplicate gallbladder that was confirmed by a neonatal precise diagnosis of a Type 2, H or ductular duplicate gallbladder, using for the first time 3D images of Magnetic resonance cholangiopancreatography in a newborn. An accurate anatomical diagnosis is mandatory in patients undergoing a possible future cholecystectomy, to avoid surgical complications or reoperations. Therefore, in case of a perinatal suspicion of a double gallbladder, neonates should undergo a Magnetic resonance cholangiopancreatography. A review of the Literature about this variant is included.